Antifungal Activity and the Chemical and Physical Stability of Microemulsions Containing Citrus hystrix DC Leaf Oil - Piyapong Pumival (2020)
© The Author(s) 2020. Citrus hystrix DC (kaffir lime) leaf oil exhibited antifungal activities against Aspergillus niger and Candida albicans. This study aimed to evaluate the antifungal activity of kaffir lime leaf oil and microemulsions containing kaffir lime oil against Trichophyton mentagrophytes var. interdigitale. The chemical components of kaffir lime leaf oil were analyzed by gas chromatography coupled with mass spectrometry. Microemulsions containing kaffir lime oil were formulated using Tween 80, propylene glycol, and water using a phase titration method. The microemulsion of kaffir lime leaf oil was evaluated for droplet size, polydispersity index, and zeta potential using a dynamic light scattering technique. The antifungal activities of kaffir lime oil and its microemulsion were investigated through macrodilution and agar well diffusion methods, respectively. The degradation of citronellal in the microemulsion was analyzed by validated UV-Visible spectrophotometry. The minimum inhibitory concentration value of kaffir lime oil was 1.08 ± 0.00 mg/mL. The microemulsion of kaffir lime leaf oil exhibited potent antifungal activity against T. mentagrophytes var. interdigitale. The size, polydispersity index, and zeta potential of freshly prepared microemulsion were 12.82 ± 0.40 nm, 0.183 ± 0.072, and −7.87 ± 0.06 mV, respectively. The microemulsion of kaffir lime leaf oil also demonstrated good physical and chemical stability at specific temperatures. The kaffir lime oil microemulsion was highly stable when stored at 4 °C and 30 °C for 1 month but was unstable at 45 °C. The microemulsion of kaffir lime leaf oil may be an alternative therapeutic against tinea pedis caused by T. mentagrophytes var. interdigitale.